REDUCING BLOOD PRESSURE IN ELDERLY WITH STAGE 2 PRIMARY HYPERTENSION USING SLOW DEEP BREATHING EXERCISE INTERVENTION - Ridhoyanti Hidayah; Niluh Gita Dharmahita Krisnadeva (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Elderly with hypertension is a phenomenon that is currently widely encountered in society. Uncontrolled hypertension in the elderly can cause various conditions that will affect the productivity and quality of life of the elderly. Objective: The purpose of this scientific work is so that students are able to carry out gerontic nursing care, namely assessment, diagnosis, intervention, implementation and evaluation in the elderly with hypertension. Methods: The method used is a case study of nursing care for the elderly with hypertension. This research was conducted by providing slow deep breathing exercise interventions to the elderly with hypertension as an effort to reduce blood pressure. There is non-pharmacological nursing care to maintain normal blood pressure so that the elderly can maintain their condition. Slow deep breathing exercise is a relaxation technique to lower blood pressure. Result: After being given the slow deep breathing exercise intervention to the client for 11 days and carried out 2 times a day there was a decrease in blood pressure in the client with the average decrease in systolic blood pressure in the client was 16.7 mmHg and the average decrease in diastolic blood pressure in the client was 6 ,7 mm Hg. Conclusion: It is recommended for nurses to provide slow deep breathing exercise therapy to elderly clients with hypertension as a companion to hypertension treatment to reduce blood pressure.